Impact of thyroid hormones on predicting the occurrence of persistent inflammation, immunosuppression, and catabolism syndrome in patients with sepsis - Zhang, Ling; Tan, Ruoming; Pan, Tingting; Qu, Hongping (Frontiers in Endocrinology, 2024)
Background: Persistent inflammation, immunosuppression and catabolism syndrome (PICS) prevalence has an upward trend in sepsis patients, which could be associated with poor outcomes. Thyroid hormone is expected to be correlated with inflammation, immunity and metabolism. Thus, the purpose of this study was to evaluate the effect of thyroid hormone on the occurrence of PICS, then further explore the optimal level of it in sepsis.This retrospective observational study used the online database Medical Information Mart for Intensive Care (MIMIC)-IV. Univariate and multivariate logistic regression analyses were employed to determine correlations between thyroid hormone levels and PICS. A combination of independent PICS development factors was established with accuracy assess using the area under the receiver operating characteristic curve (AUC-ROC).Results: Patients were divided into PICS (n=205) and non-PICS (n=671) group. Third quartiles of triiodothyronine (T3) (60-80ng/dl) and thyroxine (T4) (5.5-6.8ug/dl) had the lowest PICS incidence; the adjusted odds ratio (OR) was 0.33 (T3, p=0.009) and 0.39 (T4, p=0.006) compared with 1st quartiles of T3 and T4. For patients with pre-existing T3 deficiency, severe deficiency (T3 <60ng/dl) and high Sequential Organ Failure Assessment (SOFA) score were significantly related with PICS incidence. The AUC for these combined parameters in predicting PICS occurrence was 0.748 (all patients) and 0.861 (patients without thyroid disease).Conclusions: Mild T3 deficiency (60-80ng/dl) was significantly associated with the lowest risk-adjusted PICS occurrence in patients with sepsis. Severe T3 deficiency (<60ng/dl) and SOFA score were independent risk factors for PICS occurrence.